Salvage interstitial brachytherapy based on computed tomography for recurrent cervical cancer after radical hysterectomy and adjuvant radiation therapy: case presentations and introduction of the technique - Liu, Zhong-Shan (J Contemp Brachytherapy, 2016)
PURPOSE: Locally recurring cervical cancer after surgery and adjuvant radiotherapy remains a major therapeutic challenge. This paper presents a new therapeutic technique for such patients: interstitial brachytherapy (BT) guided by real-time three-dimensional (3D) computed tomography (CT). MATERIAL AND METHODS: Sixteen patients with recurrent cervical cancer after radical surgery and adjuvant external-beam radiotherapy (EBRT) were included in this study. These patients underwent high-dose-rate (HDR) interstitial BT with free-hand placement of metal needles guided by real-time 3D-CT. Six Gy in 6 fractions were prescribed for the high-risk clinical target volume (HR-CTV). D(90) and D(100) for HR-CTV of BT, and the cumulative D(2cc) for the bladder, rectum, and sigmoid, including previous EBRT and present BT were analyzed. Treatment-related complications and 3-month tumor-response rates were investigated. RESULTS: The mean D(90) value for HR-CTV was 52.5 ± 3.3 Gy. The cumulative D(2cc) for the bladder, rectum, and sigmoid were 85.6 ± 5.8, 71.6 ± 6.4, and 69.6 ± 5.9 Gy, respectively. The mean number of needles was 6.1 ± 1.5, with an average depth of 3.5 ± 0.9 cm for each application. Interstitial BT was associated with minor complications and passable tumor-response rate. CONCLUSIONS: Interstitial BT guided by real-time 3D-CT for recurrent cervical cancer results in good dose-volume histogram (DVH) parameters. The current technique may be clinically feasible. However, long-term clinical outcomes should be further investigated.